Detection of Novel Orthobunyavirus Reassortants in Fatal Neurologic Case in Horse and Culicoides Biting Midges, South Africa - Matshepo Elizabeth Rakaki; Miné van der Walt; June Williams; Marietjie Venter (Emerging Infectious Diseases)
We detected Shuni virus in horses and ovine fetuses and Shamonda virus in a caprine fetus in South Africa. We identified a Shuni/Shamonda virus reassortant in a horse and Shuni/Caimito, Shamonda/Caimito, and Shamonda/Sango virus reassortants in Culicoides midges. Continued genomic surveillance will be needed to detect orthobunyavirus infections in Africa.